2012
DOI: 10.1111/febs.12031
|View full text |Cite
|
Sign up to set email alerts
|

Electron transport during aceticlastic methanogenesis by Methanosarcina acetivorans involves a sodium‐translocating Rnf complex

Abstract: The anaerobic methanogenic archaeon Methanosarcina acetivorans lives under extreme energy limitation. Methanogenesis from acetate as carried out by M. acetivorans involves an anaerobic electron transport chain with ferredoxin as electron donor and heterodisulfide as electron acceptor, and so far only the heterodisulfide reductase has been shown to translocate H + . Here, we describe a second Na + -translocating coupling site in this electron transport chain. Inside-out membrane vesicles of M. acetivorans catal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
102
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(112 citation statements)
references
References 46 publications
9
102
1
Order By: Relevance
“…A physiological role is envisioned for the Mrp complex of M. acetivorans in adjusting the Na ϩ /H ϩ ratio optimally for ATP synthesis by the ATP synthase and thereby increasing the thermodynamic efficiency of acetate conversion to methane. The proposed role is based on results presented here, recent genetic evidence that the Rnf complex generates a high external Na ϩ gradient (14), and that activity of the ATP synthase is concurrently coupled to both Na ϩ and H ϩ (15). In the pathway of acetate conversion to methane (Fig.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…A physiological role is envisioned for the Mrp complex of M. acetivorans in adjusting the Na ϩ /H ϩ ratio optimally for ATP synthesis by the ATP synthase and thereby increasing the thermodynamic efficiency of acetate conversion to methane. The proposed role is based on results presented here, recent genetic evidence that the Rnf complex generates a high external Na ϩ gradient (14), and that activity of the ATP synthase is concurrently coupled to both Na ϩ and H ϩ (15). In the pathway of acetate conversion to methane (Fig.…”
Section: Discussionmentioning
confidence: 87%
“…The combined evidence supports a H 2 -independent membrane-bound electron transport chain originating with Fd and culminating with reduction of CoM-S-S-CoB that involves the Rnf complex, cytochrome c, and MP. More recently, it was reported that inverted membrane vesicles of M. acetivorans catalyze Na ϩ transport coupled to the oxidation of Fd and reduction of CoM-S-S-CoB (14). It was further reported that a ⌬rnf mutant is unable to grow with acetate and that Na ϩ transport coupled to Fd:CoM-S-S-CoB oxidoreductase activity of membranes is abolished (14), which supports a role for the Rnf complex in generation of a Na ϩ gradient supplementing the Na ϩ gradient generated by Mtr.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The dissimilarity of this pivotal reaction step in aceto-and methanogens is thus a further entry into the list of observations suggesting a deep cleft between the two types of WL pathways. The recent finding that a Rnf complex plays a crucial role in a methanogenic Archaeon [41] might be taken to contradict this line of argument. A search of protein sequence databases was performed using BLAST to identify the occurrence of functional equivalents (homologues) of rnf genes among organisms.…”
Section: Introductionmentioning
confidence: 99%
“…A role for the Mrp complex in M. acetivorans was previously proposed, where the complex adjusts the ratio of Na ϩ and H ϩ gradients optimally for driving ATP synthesis by sodium-and protondependent ATP synthase during growth with acetate (15). The genomes of M. burtonii and M. methylutens in clade II are annotated with genes encoding subunits of the canonical membrane-bound Rnf complex shown to pump Na ϩ during electron transport in M. acetivorans (30,31). The Rnf complex in these methylotrophic methanogens has the potential for participation in the membrane-bound electron transport chain that also generates a H ϩ gradient, in addition to a Na ϩ gradient (32).…”
Section: Resultsmentioning
confidence: 99%